The Phenomenon of Cyber Bullying: Interpretation, Confrontation, and the Position of Islamic Law (Journal of Namibian Studies : History Politics Culture, 2023)
This research dealt with the phenomenon of cyber bullying, indicating its causes and means of combating it, and the position of Islamic law towards it. However, its importance lies in the fact that it studies an extremely dangerous phenomenon that must be addressed, because of its devastating and dangerous effects that threaten society and its members. Moreover, it is necessary to reveal its causes and characteristics of its offenders, with the aim of developing policies that enable to confront it, in order to reach solutions to limit its spread, and help specialists and officials. in all fields to put those policies and solutions into practice.For this purpose, the researchers herein relied on the descriptive and analytical approaches.The research concluded a number of results, the most important of which are; Islamic law preceded the prohibition of bullying in all its forms, in order to protect the Muslim community from this phenomenon and its negative effects. Also, that the phenomenon of cyber bullying is one of the negative aspects of social networking sites. In addition, that the real motives driving cyber bullying behavior differ from one person to another, but in the end it reverts to the interaction of a group of internal and external factors. Based on these results, the researchers recommend the necessity of concerted efforts of the family, educational institutions and governments to address the phenomenon of cyber bullying, develop preventive measures and remedial measures to combat it comprehensively, and work to publish good media content that promotes the values of equality, love and tolerance, and devotes the concept of constructive social communication and its development, and contributes to reducing the impact of cyber bullying on society. In addition to imposing effective censorship on electronic means of communication, especially social media, obliging those in charge of them to monitor their users, and banning the accounts of those who re-practice cyber bullying, after alerting them the first time. Finally, enacting the necessary laws to define cyber bullying behaviors, and imposing heavy penalties on its perpetrators.